Lifelong learning tendencies of trainers in adult education - Şener Şentürk; Volkan Duran (International Journal of Evaluation and Research in Education (IJERE), 2020)
Life-long learning competencies, skills and attitudes are of having significance for education processes. The study was designed based on the correlational survey model. Population consists of 354 trainers in Public Education Centers in Samsun. In terms gender, there was a significant difference in lack of regulation and lack of curiosity dimension in favour of females in terms of lifelong learning tendencies. It was found that as the age level increases, the tendency to persistence which is the sub-factor of lifelong tendencies increases. It was found that as the level of education increases, persistence level decreases and regulation skill increases. No statistically significant difference was found between the mean scores of lifelong learning tendencies in terms of professional seniority variable and mode of their work. It was seen that the trainers who did not receive pedagodical formation had higher tendency in the fields of motivation and persistence. It was found that there was a significant difference in the sub-dimension of lack of regulation of learning according to the existance of any curriculum related to their field of study in favour of saying “no”.